2012
DOI: 10.1371/journal.ppat.1002964
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Gametocyte Development 1 (Pfgdv1) and Gametocytogenesis Early Gene Identification and Commitment to Sexual Development

Abstract: Malaria transmission requires the production of male and female gametocytes in the human host followed by fertilization and sporogonic development in the mosquito midgut. Although essential for the spread of malaria through the population, little is known about the initiation of gametocytogenesis in vitro or in vivo. Using a gametocyte-defective parasite line and genetic complementation, we show that Plasmodium falciparum gametocyte development 1 gene (Pfgdv1), encoding a peri-nuclear protein, is critical for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
160
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(171 citation statements)
references
References 79 publications
11
160
0
Order By: Relevance
“…In each asexual cycle of the P. falciparum blood-stage, a small subpopulation of parasites converts to the sexual gametocyte form required for transmission to the mosquito vector. Recently, genetic determinants for sexual differentiation have been identified in P. falciparum (Eksi et al, 2012; Ikadai et al, 2013; Rovira-Graells et al, 2012; Silvestrini et al, 2010; Young et al, 2005). However, the molecular basis for the frequency of switching from the asexual cycle to sexual development remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In each asexual cycle of the P. falciparum blood-stage, a small subpopulation of parasites converts to the sexual gametocyte form required for transmission to the mosquito vector. Recently, genetic determinants for sexual differentiation have been identified in P. falciparum (Eksi et al, 2012; Ikadai et al, 2013; Rovira-Graells et al, 2012; Silvestrini et al, 2010; Young et al, 2005). However, the molecular basis for the frequency of switching from the asexual cycle to sexual development remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, gametocyte maturation and gametocytogenesis are accompanied by the coordinated expression of adhesive proteins, such as the epidermal growth factor domain-containing proteins P. falciparum s25 (Pfs25) and P. falciparum s28 (Pfs28), the 6-Cys proteins P. falciparum s230 (Pfs230) and P. falciparum s48/45 (Pfs48/45), and the LCCL domain-containing P. falciparum CCp (PfCCp) proteins (20)(21)(22)(23). Recent work has also identified the P. falciparum gametocyte development 1 (Pfgdv1) gene as being critical for gametocyte production (24). In addition, transcriptomic data demonstrate significant changes in a subset of genes immediately following malaria parasite transmission to the mosquito (17).…”
mentioning
confidence: 99%
“…In 2012, Eksi et al . showed that gametocyte development 1 (GDV1), a perinuclear Plasmodium falciparum protein, plays a role in gametocytogenesis [1]. GDV1 overexpression enhanced gametocyte formation, whereas gdv1 -deleted parasite lines were gametocyte deficient.…”
mentioning
confidence: 99%
“…These data further substantiate the earlier finding by Eksi et al . [1] that overexpression of Pfgdv1 modulates gametocytogenesis in a dynamic fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation